2015
DOI: 10.1007/s00381-015-2750-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI demonstrating vein of Galen malformations in two successive pregnancies—a previously unreported occurrence

Abstract: This case demonstrates that fetal MRI is a powerful tool in the investigation of in utero neurovascular malformations. A genetic mutation was identified, but this was of uncertain significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…Most cases involved loss-of-function variants (Figure 1), which is consistent with the type of variants commonly reported in postnatal cases (Revencu et al, 2008;Revencu et al, 2013;Wooderchak-Donahue et al, 2018). Three had a missense variant, but these were most likely benign, considering they were identified either in combination with a loss-of-function variant (ID 24, Revencu et al, 2013) or inherited from an asymptomatic mother in fetuses that were not tested for EPHB4 (Kwong et al, 2015).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Most cases involved loss-of-function variants (Figure 1), which is consistent with the type of variants commonly reported in postnatal cases (Revencu et al, 2008;Revencu et al, 2013;Wooderchak-Donahue et al, 2018). Three had a missense variant, but these were most likely benign, considering they were identified either in combination with a loss-of-function variant (ID 24, Revencu et al, 2013) or inherited from an asymptomatic mother in fetuses that were not tested for EPHB4 (Kwong et al, 2015).…”
supporting
confidence: 72%
“…Prenatal presentation of CM-AVM is unusual. A total of 15 cases have been reported so far (Table 1; Durrington et al, 2013;Grillner et al, 2016;Kwong et al, 2015;Macmurdo et al, 2016;Overcash et al, 2015;Revencu et al, 2013;Saliou et al, 2017), most of them presenting with intracranial AVM or AVF detected on ultrasound (10/15).…”
mentioning
confidence: 99%
“…Fetal MRI is now the preferred modality for diagnosing fetal central nervous system (CNS) abnormalities because of its advantages over ultrasonography[ 2 , 27 , 28 ]. Prenatal MRI and MR angiography can identify the prognostic factors (cardiac failure, polyhydramnios, pericardial and pleural effusion, ascites, fetal hydrops, and brain injury) that affect prenatal counseling and aid in delineating the blood supply to the lesion for planning postnatal management[ 2 , 27 - 29 ]. Yuval et al[ 15 ], while enumerating the prognostic features for VGAMs have suggested that neonates with cardiomegaly, dilated vena cava or jugular vein, retrograde aortic flow and multiple feeder arteries may have a better prognosis if there is immediate intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно данным литературы, у мальчиков АВГ встречается примерно в 2 раза чаще по сравнению с девочками [12,13]. Вероятность рождения ребенка с АВГ при последующих беременностях чрезвычайно мала [14]. Выявленные в отдельных наблюдениях АВГ мутации генов ENG (эндоглина) [15] и RASA1 [16] не могут служить доказательством генетической природы данной мальформации.…”
unclassified
“…В последние годы высокоэффективным методом диагностики АГМ у плода считается магнитно-резонансная томография [26,27]. По сравнению с УЗИ МРТ-исследование имеет ряд преимуществ, поскольку позволяет выявить особенности строения сосудистых мальформаций [14], а также сочетанные аномалии развития головного мозга [28]. Применение пренатальной МРТ рекомендуется и для дифференциальной диагностики АВГ [26,27].…”
unclassified